Strength training for fat loss - Tumminello, Nick (Human Kinetics, 2014)
This book explains how to use the 3 Cs of metabolic strength training-circuits, combinations and complexes. This book provides more than 150 exercises using barbells, dumbbells, resistance bands, machines and body weight, as well as realistic nutrition recommendations for staying healthy, maintaining muscle and regulating metabolism